The Mann-Kendall Test for Temperature Trends in Some Selected Stations in Iraq - Al-Tmimi, Amani I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, Mann-Kendall test was used to investigate the existence of possible deterministic and stochastic climatic trends in (Baghdad,Basrah,Mosul,Al-Qaim) stations. The statistical test was applied to annual monthly mean of temperatures for the period (19932009). The values of S-statistic were (62, 44, 52, 64) by comparing these values with the table of null probability values for S we get a probability of (0.002, 0.026, 0.010, 0.002) this result is less than Î± for the 95% confidence level (Î± = 0.05) indicating a significant result at this level of confidence. Concluded that an increasing trend in concentration is present at the 95% confidence level and the variance of the S-statistic is calculated and it is compared to the table of null probability values for Z and our conclusion reject the null, there is an increasing of trend.